The evolution of the returns to human capital in Canada, 1980-2005 - Brahim Boudarbat; Thomas Lemieux; W. Craig Riddell (Institute for the Study of Labor (IZA), 2010)
We examine the evolution of the returns to human capital in Canada over the period 1980-2005. Our main finding is that returns to education increased substantially for Canadian men, contrary to conclusions reached previously. Most of this rise took place in the early 1980s and since 1995. Returns to education also rose, albeit more modestly, for Canadian women. Another important development is that after years of expansion, the wage gap between younger and older workers stabilized after 1995. Controlling for work experience and using Canadian Census data appear to account for the main differences between our results and earlier findings.
Keywords: J24; J31; 330; Human capital; wage differentials; Canada; Bildungsertrag; Lohnstruktur; Berufserfahrung; Kanada